Simulation of tight fluid flow with the consideration of capillarity and stress-change effect - Yuan Zhang (Nature Portfolio, 2019)
Abstract The horizontal wells and multi-stage hydraulic fracturing technologies play a significantly important role in developing unconventional reservoirs. Due to the nanopore effects and stress deformation in tight formations, the fluid equilibrium and thermodynamics become more complex and the conventional reservoir simulation models cannot accurately handle these mechanisms. Hence, the objective of this work is to propose a comprehensive simulation model considering the effects of confined space and stress-dependent deformation. We first evaluated the phase envelope and fluid properties in the confined nanopores. Results show that bubble-point pressure and oil viscosity decrease, while formation volume factor and gas-oil ratio increase. The heavy components cause large deviation on the P-T phase envelope at the reservoir condition. Subsequently, a reservoir simulation model of the Bakken tight oil reservoir was built including the effect of stress-dependent deformation. The proposed phase behavior model was applied into the reservoir simulator to predict the hydrocarbon production from the Bakken tight oil reservoir. Finally, the role of the confined space and the stress-dependent deformation on the production are examined in detail. This novel simulation approach can shed light on the better understanding of the key parameters affecting well production of in developing tight oil reservoirs in the future.